Failure to follow up on a medically actionable finding from direct to consumer genetic testing: A case report. Issue 6 (23rd April 2020) - Garmany, Ramin; Lee, Christopher J.; Sharp, Richard R.; Kullo, Iftikhar J.
Abstract: Background: A 61‐year‐old woman underwent direct to consumer genetic testing and was found to be homozygous for the C282Y HFE variant (c.845G>A :p.Cys282Tyr) which is classified as pathogenic/likely pathogenic for hereditary hemochromatosis. However, no action was taken by the individual. Methods: The individual took part in the Mayo Clinic Return of Actionable Variants Empiric (RAVE) study and the actionable finding was confirmed and results disclosed in person by a genetic counselor with subsequent referral to a hepatologist. Results: Further testing revealed iron overload with an elevated ferritin level (560 ng/ml) and increased ferritin saturation (74%). Phlebotomy was initiated with subsequent normalization of the ferritin levels (252 ng/ml). Conclusion: This case highlights that actionable genetic results may not be acted on after direct to consumer testing and the need for effective genetic counseling after such testing. Abstract : We describe the case of a 61‐year‐old woman who was found to be homozygous for the C282Y HFE variant on direct to consumer genetic testing but only took action when the result was returned by a genetic counselor as part of a subsequent research study. This case highlights that actionable genetic results may not be acted on after direct to consumer testing and the need for effective genetic counseling after such testing.